Prevalence and Epidemiological Profile of Medico-legal Cases of Suicidal Autopsy at a Tertiary Care Hospital of Central Nepal - Shrestha, Kaschev; Upreti, Arish; Gurung, Praful; Shah, Dhiraj; Shrestha, Natasha; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2024)
Background A medico-legal case (MLC) arises from an unnatural incident causing physical harm, necessitating intervention and legal resolution. MLCs integrate medical and legal aspects, requiring both a physician's assessment and an investigation by law enforcement, often involving autopsy. The objective of this study was to find the prevalence and epidemiological profile of medico-legal autopsy cases of suicide at a tertiary care hospital of central Nepal. Methods A retrospective cross-sectional study conducted at College of Medical Sciences, Bharatpur, Chitwan, Nepal, between December, 2023 and February, 2024 on suicidal autopsy cases. Suicidal autopsy data of last three years (from 2077/78 to 2079/80) were collected from the Bharatpur hospital's autopsy record file. Descriptive statistical tools were used for data analysis. For, categorical variables frequency and percentage were calculated while mean and standard deviation were used for continuous variables. Data was entered and analyzed by using SPSS-20. Results The prevalence of Medico-legal cases of suicidal autopsy in Chitwan district in last three year is 29.16% (with 95% CI as 27.23% to 31.16%). The trend of suicidal autopsy in last three year is in increasing trend in this area. Majority (21.86%) of suicidal cases were in the age group 46-60 years. Male (64.11%) cases dominated female cases in Suicidal autopsy. Majority (34.42%) of suicidal attempt was at 6-12:00 noon and the most common method of suicidal attempt cases were by hanging (81.57%). Most of the case were in Monday and in occurred in Ashoj. Conclusions The trend of suicidal autopsy in the last three year is in increasing trend in central Nepal. Among the total autopsy cases, prevalence of suicidal autopsy is one third. The burden of suicidal cases is significantly high among male